Effect of Feeding Balanced Ration on Solids-Not-Fat Content of Milk and Production Performance of Lactating Crossbred Cows - Bhanderi, B.M.; Garg, M.R.; Goswami, Ajay; Shankhpal, Sachin (Indian Journal of Animal Nutrition, 2018)
A study was undertaken to investigate the effect of feeding a balanced ration on the solids-not fat (SNF) content of milk and production performance of crossbred cows (n=70) in Anand district of Gujarat, India. OutÂ of 115 animals, 70 crossbred cows showed low SNF content. Milk yield, milk fat, SNF and net daily income of milk producers were recorded before and after feeding a balanced ration. Nutritional status of animals indicated that about 76% of the animals were given excess protein and energy in the ration, whereas, ration of 83% of the animals was deficit in calcium and phosphorus. On feeding a balanced ration for 8 weeks, there was improvement (P<0.01) in SNF content of milk from 7.88 to 8.65%. Average daily milk yield increased (P<0.01) from 10.60 to 11.77 kg and milk fat from 4.12 to 4.21% on feeding a balanced ration. This translated into an additional daily monetary benefit of about ` 45 per animal to the milk producers. Milk production efficiency of fat corrected milk (kg FCM produced/kg DMI consumed) increased from 0.69 to 0.90 and rumen microbial protein increased from 735 to 1197 g/d (38%) on feeding a balanced ration. The levels of serum immunoglobulins like Ig G, Ig M and Ig A increased from 21.42 to 26.73, 2.74 to 3.44 and 0.42 to 0.53 mg/ml, respectively whereas the level of Ig E decreased from 215 to 142 pg/ml on feeding a balanced ration. The study revealed that feeding of a balanced ration not only helped in improving SNF content of milk but also resulted in improved immune status, microbial protein synthesis and daily income of milk producers.